(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
According to the World Health Organization (WHO). Modern laboratory diagnostics play a crucial role in assessing disease severity, identifying its etiology, and monitoring treatment effectiveness. This article provides a detailed overview of methods for detecting inflammation biomarkers, specific IgE, eosinophils, fractional exhaled nitric oxide (FeNO), and the role of genetic studies. Recent advancements and their significance in a personalized approach to asthma management are discussed.